HDAC6 selective inhibition of melanoma patient T-cells augments anti-tumor characteristics - Andressa S. Laino; B. C. Betts; A. Veerapathran; I. Dolgalev; A. Sarnaik; S. N. Quayle; S. S. Jones; J. S. Weber; David M. Woods (Journal for ImmunoTherapy of Cancer, 2019)
Abstract Background Therapies targeting anti-tumor T-cell responses have proven successful in the treatment of a variety of malignancies. However, as most patients still fail to respond, approaches to augment immunotherapeutic efficacy are needed. Here, we investigated the ability of histone deacetylase 6 (HDAC6)-selective inhibitors to decrease immunosuppression and enhance immune function of melanoma patient T-cells in ex vivo cultures. Methods T-cells were harvested from peripheral blood or tumor biopsies of metastatic melanoma patients and cultured in the presence of pan-, class-specific or class-selective histone deacetylase (HDAC) inhibitors. Changes in cytokine production were evaluated by Luminex and intracellular flow cytometry staining. Expression of surface markers, transcription factors, protein phosphorylation, and cell viability were assessed by flow cytometry. Changes in chromatin structure were determined by ATAC-seq. Results T-cell viability was impaired with low doses of pan-HDAC inhibitors but not with specific or selective HDAC inhibitors. The HDAC6-selective inhibitors ACY-1215 (ricolinostat) and ACY-241 (citarinostat) decreased Th2 cytokine production (i.e. IL-4, IL-5, IL-6, IL-10 and IL-13). Expansion of peripheral blood T-cells from melanoma patients in the presence of these inhibitors resulted in downregulation of the Th2 transcription factor GATA3, upregulation of the Th1 transcription factor T-BET, accumulation of central memory phenotype T-cells (CD45RA-CD45RO + CD62L + CCR7+), reduced exhaustion-associated phenotypes (i.e. TIM3 + LAG3 + PD1+ and EOMES+PD1+), and enhanced killing in mixed lymphocyte reactions. The frequency, FOXP3 expression, and suppressive function of T regulatory cells (Tregs) were decreased after exposure to ACY-1215 or ACY-241. Higher frequencies of T-cells expressing CD107a + IFNγ+ and central memory markers were observed in melanoma tumor-infiltrating lymphocytes (TIL), which persisted after drug removal and further expansion. After ACY-1215 treatment, increased chromatin accessibility was observed in regions associated with T-cell effector function and memory phenotypes, while condensed chromatin was found in regions encoding the mTOR downstream molecules AKT, SGK1 and S6K. Decreased phosphorylation of these proteins was observed in ACY-1215 and ACY-241-treated T-cells. AKT- and SGK1-specific inhibition recapitulated the increase in central memory frequency and decrease in IL-4 production, respectively, similar to the observed effects of HDAC6-selective inhibition. Conclusions HDAC6-selective inhibitors augmented melanoma patient T-cell immune properties, providing a rationale for translational investigation assessing their potential clinical efficacy.